Scintillation measurement on ku-band satellite path in tropical climate - Hassan , Dao; Islam, Md. Rafiqul; Chebil, Jalel; Khalid, Khateeb (2013)
Scintillation data was collected in Kuala Lumpur, Malaysia for one year measurement. The data were obtained from MEASAT3 satellite operating at Ku-band with elevation angle of 77.4˚. In this paper, scintillation statistics are analysed in dry (non-rain) condition. The scintillation distributions are represented scintillation intensity and amplitude by monthly, seasonal, worst-month and annual distributions. Probability density function (PDF) of scintillation intensity correspondingly agrees to Generalize Extreme Value (GEV) fit. In addition, model validation to the measured data is also provided.